2022
DOI: 10.3889/oamjms.2022.8939
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice on Cervical Cancer and HPV Vaccination among Medical Students in Jakarta, Indonesia: A Cross-Sectional Study

Abstract: BACKGROUND: Cervical cancer is the second-most common cancer in Indonesian women. While the cervical cancer screening has been integrated in Indonesian primary health-care facilities, the HPV vaccination has not yet become a national program. AIM: The objective of this research was to measure the knowledge, attitude, and behavior of medical students in Jakarta toward cervical cancer and its prevention. The result of this study could be implemented to develop a more comprehensive national educational program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Although based on WHO recommendations, HPV vaccines are effective if administered before the start of sexual activity and exposure to HPV infection [1], our study found that only 7.6% of female students were vaccinated. The findings from our study are aligned with several other studies that have also reported low levels of HPV vaccination among students, although in a slightly lower percentage than our study [11,32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although based on WHO recommendations, HPV vaccines are effective if administered before the start of sexual activity and exposure to HPV infection [1], our study found that only 7.6% of female students were vaccinated. The findings from our study are aligned with several other studies that have also reported low levels of HPV vaccination among students, although in a slightly lower percentage than our study [11,32].…”
Section: Discussionsupporting
confidence: 92%
“…Data was collected using a Google questionnaire form, sent to female students via email. The questionnaire was prepared using a method of combining the WHO guidelines on conducting a KAP survey study [9] and similar questionnaires from several published KAP studies related to cervical cancer [10][11][12][13]. The survey questionnaire was divided into four sections: (i) sociodemographic characteristics; (ii) knowledge; (iii) attitudes, and (iv) practices.…”
Section: Methodsmentioning
confidence: 99%